Endoscopic management of postoperative bleeding - Sung Hyeok Ryou; Ki Bae Bang (Korean Society of Gastrointestinal Endoscopy, 2023)
Postoperative gastrointestinal bleeding is a rare but serious complication that can lead to prolonged hospitalization and significant morbidity and mortality. It can be managed by reoperation, endoscopy, or radiological intervention. Although reoperation carries risks, particularly in critically ill postoperative patients, minimally invasive interventions, such as endoscopy or radiological intervention, confer advantages. Endoscopy allows localization of the bleeding focus and hemostatic management at the same time. Although there have been concerns regarding the potential risk of creating an anastomotic disruption or perforation during early postoperative endoscopy, endoscopic management has become more popular over time. However, there is currently no consensus on the best endoscopic management for postoperative gastrointestinal bleeding because most practices are based on retrospective case series. Furthermore, there is a wide range of individual complexities in anatomical and clinical settings after surgery. This review focused on the safety and effectiveness of endoscopic management in various surgical settings.